Improving hospital venous thromboembolism prophylaxis with electronic decision support. Issue 3 (26th November 2012) - Bhalla, Rohit; Berger, Matthew A.; Reissman, Stan H.; Yongue, Brandon G.; Adelman, Jason S.; Jacobs, Laurie G.; Billett, Henny; Sinnett, Mark J.; Kalkut, Gary
<x xml:space="preserve">Abstract</x> BACKGROUND Venous thromboembolism (VTE) disease prophylaxis rates among medical inpatients have been noted to be <50%. OBJECTIVE Our objective was to evaluate the effectiveness and safety of a computerized decision support application to improve VTE prophylaxis. DESIGN Observational cohort study. SETTING Academic medical center. PATIENTS Adult inpatients on hospital medicine and nonmedicine services. INTERVENTION A decision support application designed by a quality improvement team was implemented on medicine services in September 2009. MEASUREMENTS Effectiveness and safety parameters were compared on medicine services and nonmedicine (nonimplementation) services for 6‐month periods before and after implementation. Effectiveness was evaluated by retrospective information system queries for rates of any VTE prophylaxis, pharmacologic VTE prophylaxis, and hospital‐acquired VTE incidence. Safety was evaluated by queries for bleeding and thrombocytopenia rates. RESULTS Medicine service overall VTE prophylaxis increased from 61.9% to 82.1% (P < 0.001), and pharmacologic VTE prophylaxis increased from 59.0% to 74.5% (P < 0.001). Smaller but significant increases were observed on nonmedicine services. Hospital‐acquired VTE incidence on medicine services decreased significantly from 0.65% to 0.42% (P = 0.008) and nonsignificantly on nonmedicine services. Bleeding rates increased from 2.9% to 4.0% (P < 0.001) on medicine services and from 7.7% to 8.6% (P = 0.043) on nonmedicine services, with nonsignificant changes in thrombocytopenia rates observed on both services. CONCLUSIONS An electronic decision support application on inpatient medicine services can significantly improve VTE prophylaxis and hospital‐acquired VTE rates with a reasonable safety profile. Journal of Hospital Medicine 2013;8:115–120. © 2012 Society of Hospital Medicine